TRENDS OF INTERCULTURAL CHANGE IN TOURISM - Radjapova Nasiba Makhmudjonovna (Bright Mind Publishing, 2025)
Cross-cultural trends are creating new opportunities in tourism, leading to the development of cultural understanding on a global scale. Tourism offers not only the opportunity to see attractions, but also to learn about and respect other cultures. Factors such as the development of technology, interest in cultural cuisine and gastronomic tourism, as well as the introduction of sustainable tourism principles, help to make travel more diverse and intimate. The open-mindedness and global connections of the younger generation also play an important role in accepting cultural differences.
Keywords: Intercultural tourism, intercultural encounter, Gastronomic tourism.